Humanized mouse liver reveals endothelial control of essential hepatic metabolic functions - Kaffe, Eleanna; Roulis, Manolis; Zhao, Jun; Qu, Rihao; Sefik, Esen; Mirza, Haris; Zhou, Jing; Zheng, Yunjiang; Charkoftaki, Georgia; Vasiliou, Vasilis; Vatner, Daniel F.; Mehal, Wajahat Z.; et al. (Cell, 2023)
Hepatocytes, the major metabolic hub of the body, execute functions that are human-specific, altered in human disease, and currently thought to be regulated through endocrine and cell-autonomous mechanisms. Here, we show that key metabolic functions of human hepatocytes are controlled by non-parenchymal cells (NPCs) in their microenvironment. We developed mice bearing human hepatic tissue composed of human hepatocytes and NPCs, including human immune, endothelial, and stellate cells. Humanized livers reproduce human liver architecture, perform vital human-specific metabolic/homeostatic processes, and model human pathologies, including fibrosis and non-alcoholic fatty liver disease (NAFLD). Leveraging species mismatch and lipidomics, we demonstrate that human NPCs control metabolic functions of human hepatocytes in a paracrine manner. Mechanistically, we uncover a species-specific interaction whereby WNT2 secreted by sinusoidal endothelial cells controls cholesterol uptake and bile acid conjugation in hepatocytes through receptor FZD5. These results reveal the essential microenvironmental regulation of hepatic metabolism and its human-specific aspects. [Display omitted] •Development of a comprehensive and functional human hepatic tissue in a mouse host•Modeling NAFLD and fibrosis in human cells in vivo•Key metabolic functions of human hepatocytes are controlled by NPCs•WNT2 controls cholesterol uptake and bile acid conjugation in hepatocytes through FZD5 A comprehensive human liver tissue was established in a mouse host that consists of all human-relevant parenchymal and non-parenchymal cell types and mimics the cellular composition, histological architecture, and functional properties of a human liver. This highly human-relevant murine model allows investigation of human-specific metabolic features and liver cell type interactions.